Sex differences in clinical and polysomnographic features of obstructive sleep apnea: The Turkish sleep apnea database (TURKAPNE) cohort - Pihtili, A.; Peker, Y.; Akkoyunlu, M.E. (Sleep Medicine, 2025)
Background: Previous reports from relatively small clinical cohorts have suggested that the clinical presentation of obstructive sleep apnea (OSA) differs between men and women. Objective: We aimed to explore sex differences in clinical and polysomnographic features of OSA in a large nationwide registry. Methods: Participants from the ongoing Turkish Sleep Apnea Database (TURKAPNE) Study from 34 centers were included in the current analysis. OSA was defined as an apnea-hypopnea index (AHI) ≥5 events/hour and was classified as mild, moderate, and severe according to AHI cut-offs 5, 15, and 30 events/hour, respectively. Results: In all, 7130 patients (2259 women) were included. OSA was observed in 6323 (88.7 %), of whom 70.2 % were male and 29.8 % were female. In the OSA group, women were older (56.7 ± 11.9 vs. 49.5 ± 11.3 years; p < 0.001) and more obese (body mass index 34.3 ± 7.2 vs. 31.4 ± 5.6 kg/m2; p < 0.001) and had lower AHI (29.8 ± 24.1 vs. 36.8 ± 26.2 events/h; p < 0.001) than men. Loud snoring and witnessed apnea were more common in men than in women whereas women were more frequently presented with insomnia, headache, and mood changes. Women had significantly less total sleep time, less sleep efficiency, and longer sleep latency compared with men (p < 0.001 for each). Additionally, comorbid diseases such as diabetes mellitus, hypertension, asthma, psychiatric disorders, hypothyroidism as well as drug use were more common in women than in men independent of age and obesity (p < 0.05 for each). Conclusions: Our results suggest significant sex differences in clinical and polysomnographic features in this nationwide Turkish adult population. Women with OSA have more symptom burden and comorbidities despite having a less severe AHI. © 2024 The Authors
Keywords: Obstructive sleep apnea; Polysomnography; Sex; Symptoms; acetylsalicylic acid; alpha adrenergic receptor blocking agent; angiotensin receptor antagonist; anticonvulsive agent; antidiabetic agent; antihistaminic agent; beta adrenergic receptor blocking agent; calcium channel blocking agent; clopidogrel; dipeptidyl carboxypeptidase inhibitor; diuretic agent; insulin; montelukast; neuroleptic agent; nonsteroid antiinflammatory agent; proton pump inhibitor; warfarin; adult; alcohol consumption; algorithm; anthropometric parameters; apnea; apnea hypopnea index; Article; asthma; auditory stimulation; Beck Depression Inventory; body mass; clinical dementia rating scale; clinical feature; cohort analysis; controlled study; demographics; depression; diabetes mellitus; dyspnea; educational status; electromyography; Epworth sleepiness scale; ethnicity; fatigue; female; headache; heart arrhythmia; heart rate; hip circumference; human; hypertension; hypothyroidism; insomnia; life expectancy; lung function test; major clinical study; male; mandibular advancement; mental disease; middle aged; mood change; neck circumference; nocturia; obesity; obstructive sleep apnea; oxygen desaturation; oxygen saturation; periodic limb movement disorder; Pittsburgh Sleep Quality Index; polysomnography; quality control; questionnaire; REM sleep; restless legs syndrome; risk factor; self report; sex difference; sleep; sleep apnea syndromes; sleep efficiency; sleep latency; sleep quality; sleep time; smoking; snoring; symptom burden